Analysis of Students' Mathematical Reasoning Ability and Self-Confidence In Solving Problem-Based Questions - Anggerayni, Annisa; Ikashaum, Fertilia (Al-Khawarizmi, 2024)
Analysis of students' mathematical reasoning abilities and self-confidence in solving problems based on background problems in this study, namely the low students' reasoning abilities and self-confidence in learning mathematics. This study aims to: (1) Describe the level of students' mathematical reasoning abilities in solving problem-based questions. (2) Describe the level of self-confidence of students in answering problem-based questions. This study uses a qualitative descriptive research method. Methods of data collection using: (1) Test (2) Questionnaire (3) Interview. Data analysis techniques use: (1) data reduction (2) data presentation (3) conclusion drawing. Based on the results of tests and questionnaires conducted on class VIII B students at SMP Negeri 10 Metro, this study showed that students who had reasoning abilities and high self-confidence in solving questions and questionnaires showed very good results. Meanwhile, students who have reasoning skills and self-confidence who are currently solving questions and questionnaires show quite good results. As for students who have low reasoning abilities also have a low level of self-confidence.